2001
DOI: 10.1086/322519
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetic Interactions of Nevirapine and Methadone and Guidelines for Use of Nevirapine to Treat Injection Drug Users

Abstract: Administration of nevirapine to HIV-infected injection drug users who also receive methadone results in a significant reduction in methadone exposure after 7-10 days of therapy. Many patients require an increase in methadone dose to counteract this effect.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
40
0
1

Year Published

2002
2002
2018
2018

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 98 publications
(43 citation statements)
references
References 11 publications
2
40
0
1
Order By: Relevance
“…Six subjects did not require any change in their methadone doses, despite significant reductions in methadone exposure. It has been suggested that a gradual detoxification from methadone occurs during NVP treatment (11). Our data strengthen this hypothesis because, after having increased their methadone doses, almost all of the patients still had lower methadone AUCs without any withdrawal symptoms.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Six subjects did not require any change in their methadone doses, despite significant reductions in methadone exposure. It has been suggested that a gradual detoxification from methadone occurs during NVP treatment (11). Our data strengthen this hypothesis because, after having increased their methadone doses, almost all of the patients still had lower methadone AUCs without any withdrawal symptoms.…”
Section: Discussionsupporting
confidence: 82%
“…Symptoms rarely appear within the first few days, which suggests that the effect is caused by the induction of methadone metabolism by NVP (3,11). One controlled trial involving eight patients has shown that concomitant NVP treatment substantially decreases the trough level and the area under the concentration-time curve (AUC) of methadone (11).…”
mentioning
confidence: 99%
“…Efavirenz and nevirapine both were found to reduce the plasma concentrations of methadone, resulting in withdrawal symptoms [12][13][14], and, as a consequence, the methadone dose was increased when administered with efavirenz or nevirapine [12][13][14]. In contrast, saquinavir/ritonavir and lopinavir/ritonavir were also found to decrease methadone plasma concentrations of methadone with no significant withdrawal symptoms [15,16].…”
Section: Discussionmentioning
confidence: 99%
“…Metadon tedavisi alan bir hastada kullanılmaları yoksunluk sendromları yaşanmasına neden olabilir. Nevirapin ile birlikte kullanımda metadona maruz kalmada %51 kadar azalma olduğu gösterilmiştir [47] . Nelfinavir ile birlikte kullanımda metadon klirensinde 1,7-1,8 kat artış olduğu görülmüştür [48] .…”
Section: Opiatlarunclassified